The Effectiveness Self-ACU Yoga Towards Fasting Blood Sugar Levels in Type II Diabetes Mellitus Patients - Ainun Kurniati (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Diabetes mellitus is a metabolic disease characterized by an increase in blood sugar levels (hyperglycemia). Type II diabetes mellitus can cause various complications such as hypertension, stroke, kidney failure, coronary heart disease, retinal damage and long-healed wounds leading to amputation especially in the legs. To reduce the complications caused by type II diabetes mellitus, it needs to be done conservatively, one of them is Self-Acu Yoga. Self Acu-Yoga which is a combination of breathing, relaxation and meditation techniques can stimulate the pancreas to increase the ability of the pancreas to produce insulin so that it can reduce blood sugar levels. Method The type of research used is Quasy Experiment with a pretest-posttest control group design. This study arranged two groups, namely the intervention group and the control group. Technique Non probability sampling with purposive sampling method was used to get 32 ??respondents divided into 2 groups. The intervention group was given Self Acu-Yoga, while the control group was given acupressure 3 times a week for 4 weeks. Result The result Paired t test showed a p-value value 0.001 which indicates that there are significant differences between the intervention and control groups. Conclusion The results of study after being given an intervention that there was a decrease in fasting blood sugar levels in patients who received Self-Acu Yoga, so that this action was effectively implemented for patients who experienced increased blood sugar levels, especially in patients with type II diabetes mellitus.